Green-AgNPs modified membrane for monitoring mercury ions in cosmetic sample using pre-concentration assisted voltammetry technique - Fadillah, Ganjar; Inayatussholeha, Eka Nurdina; Hidayat, Rahmat (Indonesian Journal of Chemical Analysis (IJCA), 2024)
The carcinogenic and teratogenic properties of mercury have driven the necessity for the development of highly sensitive methods capable of detecting even trace amounts of the element. In response to this need, an analysis technique has been established for mercury ions, employing preconcentration methods utilizing filter paper modified by silver nanoparticles (AgNPs) and 3-Amino propyl trimethoxy silane (APTMS). This method allows for the detection of mercury ions through the voltammetry technique, ensuring accurate and reliable results. Upon conducting analyses using this method, it was found that the tested cosmetic samples were free from Hg2+ ions, indicating the absence of mercury contamination in the cosmetics under investigation. The correlation coefficient derived from the graph of the analysis results stands at an impressive value of 0.9976, affirming the strong relationship between the measured concentrations and the actual mercury content. Additionally, the method demonstrates excellent sensitivity, as evidenced by the low limit of detection (LOD) value of 0.0483 mM and the limit of quantification (LOQ) value of 0.1611 mM.